Transformation of Legal Tender Coins into Exonumic Masonic Tokens - Cuadrado Merchán, Manuel (2025)
Exonumia is the discipline of numismatics that deals with monetized objects that lack legal tender value. In Spanish we use the term «ficha» to refer to these objects while in English they are known as token, in French jeton and in Italian gettone. Masonry also uses these objects, but with a different meaning: jetons de presence are used in the French-speaking environment while in Anglo-Saxon Masonry the tokens acquire a different function and meaning. On other occasions, legal tender coins have been used by modifying them with countermarks, overstrikes, and engravings to be used as tokens or as Masonic medals.